A Prototype of Web-based Supplementary Writing Instructional Media for Upper-Secondary Level Learners - Anisatul Faizah; Bambang Yudi Cahyono; Francisca Maria Ivone (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2024)
In an era characterized by a symbiotic relationship between the rapid growth of technology and extensive use of English, English as a Foreign Language (EFL) learners are tremendously exposed to digital forms of the language. Digital writing, consequently, has become a fundamental EFL skill to master. Ironically, it has not proliferated in ways that give access to all, notably for most upper-secondary school learners in Malang, Indonesia, where one might expect that technology is widely accessible. To address such an adverse situation and to support learners in enjoying EFL writing activities, a research and development (R&D) design was carried out to develop a prototype web-based supplementary writing materials that incorporate instructional strategies and learning approaches that enhance EFL writing skills and develop effective writing strategies in an authentic setting. The R&D process implemented Dick and Carrey’s instructional design framework (2001) which was integrated with Lee and Owen's instructional multimedia design framework (2004). The study resulted in the development of an E-Writing Site (EWS) to which the target users are encouraged to enjoy writing texts of their own choice at their own pace, as they engage in free voluntary writing within a social constructivist atmosphere. Experts and target users involved in the formative evaluation of the prototype perceived it to be useful and educative as it provides EFL learners with holistic, authentic, and meaningful writing practice. Moreover, some aspects of the prototype and its principles that require enhancement are addressed.